INSTITUTIONAL MODELS OF FINANCIAL CENTERS - Superviser: Akhmadaliyeva Nikholaxon; Mirjahon Ravshanov (The Conference Hub, 2025)
This study explores institutional models of financial centers and their significance in the global economy. Four main models are identified: market-based, bank-based, state-directed, and hybrid/offshore systems. Each model is examined through case studies of leading financial hubs, with attention to their institutional structures, regulatory frameworks, advantages, and weaknesses. A comparative analysis highlights how these models respond to challenges such as globalization and financial crises.
Keywords: Financial centers; institutional models; market-based system; bank-based system; state-directed finance; offshore finance; financial globalization; Uzbekistan; economic development; capital markets.